Human Resistin in Chemotherapy-Induced Heart Failure in Humanized Male Mice and in Women Treated for Breast Cancer - Schwartz, Daniel R. (Endocrine Society, 2013)
Resistin is a circulating mediator of insulin resistance mainly expressed in human monocytes and responsive to inflammatory stimuli. Recent clinical studies have connected elevated resistin levels with the development and severity of heart failure. To further our understanding of the role of human resistin in heart failure, we studied a humanized mouse model lacking murine resistin but transgenic for the human Retn gene (Hum-Retn mice), which exhibits basal and inflammation-stimulated resistin levels similar to humans. Specifically, we explored whether resistin underlies acute anthracycline-induced cardiotoxicity. Remarkably, doxorubicin (25mg/kg ip) led to a 4-fold induction of serum resistin levels in Hum-Retn mice. Moreover, doxorubicin-induced cardiotoxicity was greater in the Hum-Retn mice than in littermate controls not expressing human resistin (Retn(−/−)). Hum-Retn mice showed increased cardiac mRNA levels of inflammatory and cell adhesion genes compared with Retn(−/−) mice. Macrophages, but not cardiomyocytes, from Hum-Retn mice treated with doxorubicin in vitro showed dramatic induction of hRetn (human resistin) mRNA and protein expression. We also examined resistin levels in anthracycline-treated breast cancer patients with and without cardiotoxicity. Intriguingly, serum resistin levels in women undergoing anthracycline-containing chemotherapy increased significantly at 3 months and remained elevated at 6 months in those with subsequent cardiotoxicity. Further, elevation in resistin correlated with decline in ejection fraction in these women. These results suggest that elevated resistin is a biomarker of anthracycline-induced cardiotoxicity and may contribute in the development of heart failure via its direct effects on macrophages. These results further implicate resistin as a link between inflammation, metabolism, and heart disease.